PENGEMBANGAN KAMPUNG MOCO UNTUK MENINGKATKAN MINAT BACA DAN MOTIVASI PENDIDIKAN MASYARAKAT DESA JIKEN KECAMATAN TULANGAN - Risdiana Chandra Dhewy (STKIP PGRI Sidoarjo, 2020)
Literacy is the ability to read, write, enrich knowledge, skills, critical thinking skills, prioritize problem solving, communicate effectively, develop potential, and actively participate in society. A literacy culture is being promoted by the government in order to improve the quality of human resources, making individuals smart, creative, and productive. The purpose of this activity is to make Jiken Village Kampung Moco, so that the village has a community who is able to see literacy and has high educational motivation. The target of this activity is the residents of Jiken Village, Tulangan. Our program of activities includes the establishment of Kampung Moco located in the village hall of Jiken, a joyful literacy program to foster reading interest in the Jiken Village community, and coordination regarding the sustainability of community reading gardens. The community's response to this activity was quite enthusiastic, starting from children, teenager, mothers and fathers and village officials to community leaders.